Metal ceramic MAX phase composite powder for spraying and preparation method thereof

High-flowability MAX phase composite powders were prepared by spray granulation and radio frequency plasma spheroidization processes, which solved the application problems of existing powders in thermal spraying processes, realized the formation of high-performance coatings on the surface of complex parts, and reduced manufacturing costs.

CN121715564APending Publication Date: 2026-03-24ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202511962750.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-03-24

AI Technical Summary

Technical Problem

Existing MAX phase materials are difficult to use in thermal spraying processes, and existing powder structures are loose and have poor flowability, which cannot meet the spraying requirements of complex parts surfaces.

Method used

Highly fluid and stable composite powders are prepared using a two-step method of spray granulation and radio frequency plasma spheroidization. The primary powder is formed by spray granulation and then processed by radio frequency plasma spheroidization. Temperature and atmosphere are controlled to prevent material decomposition.

Benefits of technology

The prepared powder has good flowability and dense structure, making it suitable for various thermal spraying technologies. It can form a high-performance coating on the surface of complex parts, solving the application problems of existing materials on complex parts and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121715564A_ABST
    Figure CN121715564A_ABST
Patent Text Reader

Abstract

The invention discloses metal ceramic MAX-phase composite powder for spraying and a preparation method of the metal ceramic MAX-phase composite powder, and belongs to the field of metal ceramic composite materials. The method comprises the following steps: mixing Ni powder, Cr powder and Cr2AlC nano powder with deionized water, a binder and a dispersant according to a specific ratio, and carrying out wet ball milling to prepare uniform slurry; carrying out spray granulation to obtain primary spherical powder; and finally, carrying out spheroidizing treatment on the primary powder by adopting radio frequency plasma under the protection of inert gas to obtain a final product. The core of the preparation method is that through an optimized two-step process, many limitations in the application aspect of an existing MAX phase material are solved, and the composite powder which is high in sphericity degree, good in flowability, compact in interior and stable in MAX phase component is successfully prepared. The powder can be directly used for thermal spraying, and an ideal raw material is provided for preparing a high-performance MAX-phase metal ceramic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal-ceramic composite materials technology, specifically relating to a metal-ceramic MAX phase composite powder for spraying and its preparation method. Background Technology

[0002] MAX phases are three-dimensional layered metal-ceramic materials. Their unique crystal structure endows them with excellent electrical conductivity, high toughness, machinability, heat resistance, thermal shock resistance, and self-lubricating properties. Among them, the aluminum-containing MAX phase materials, through in-situ formation of oxides (mainly Al2O3) at high temperatures, can also repair micro- and nano-scale cracks in the material to a certain extent through bridging and filling effects, thereby improving the material's service reliability. MAX phase ceramics have broad application prospects in the field of high-temperature wear-resistant self-lubricating materials.

[0003] Existing MAX phase materials are mainly prepared as bulk materials through high-temperature sintering, which significantly limits the size and shape of parts, making them difficult to apply to complex components. Furthermore, the application of bulk materials is relatively costly. Modifying the surface of parts through thermal spraying offers greater economic value and flexibility. However, current material systems lack raw material powders that can be directly used in thermal spraying. Therefore, it is necessary to develop raw material powder preparation technologies to meet future engineering needs.

[0004] Thermal spraying technology, as a surface modification method, is economical and flexible; however, existing MAX phase material systems lack raw material powders that can be directly used for thermal spraying. Therefore, developing a method for preparing MAX phase composite powders suitable for thermal spraying is of great significance.

[0005] In existing technologies, such as CN110698204B, a sintering preparation method for MAX phase ceramics is disclosed. However, the material obtained through sintering in this patent is still a bulk material, which cannot be used for spraying on the surface of complex parts. Furthermore, the size and shape of the parts are limited by the size of the sintering furnace. While CN107935596B prepared MAX phase powder, observation of the powder morphology revealed that the powder is irregularly layered, with a loose structure and poor flowability, making it difficult to adapt to the requirements of thermal spraying processes. Therefore, there is an urgent engineering need to develop a high-performance MAX phase composite powder suitable for thermal spraying and its preparation method. Summary of the Invention

[0006] To address the aforementioned issues, this invention provides a metal-ceramic MAX phase composite powder for spraying and its preparation method. The method uses a two-step process (spray granulation + radio frequency plasma spheroidization) to prepare a highly fluid and compositionally stable composite powder, thus solving the problem that existing MAX phase materials are difficult to use in thermal spraying processes.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: On the one hand, the present invention proposes a method for preparing a metal-ceramic MAX phase composite powder for spraying, comprising the following process steps: S1: Spray granulation is used to prepare primary powder, as detailed below: S11: Raw material preparation: Add a certain amount of deionized water to a beaker, then add the auxiliary granulating agent and stir until uniformly dispersed; then add a certain mass ratio of Ni, Cr and Cr2AlC nano-sized solid powders to obtain the initial slurry; S12: Wet ball milling and mixing: The initial slurry is placed in a ball mill jar for thorough ball milling and dispersion mixing to ensure that the powder is fully and evenly dispersed; S13: Spray granulation: The mixed slurry is pumped into a preheated spray granulator using a peristaltic pump for spray granulation. After granulation, the powder in the powder collection tank is collected and sieved to obtain spherical primary powder with a particle size of more than 15μm. S2: Radio frequency plasma spheroidization treatment, as detailed below: S21: Spheroidizing process: The prepared primary powder is fed into an radio frequency plasma spheroidizer for spheroidizing treatment. Argon gas is continuously introduced during the spheroidizing process to avoid high-temperature decomposition of Cr2AlC. S22: Secondary sieving: After spheroidization, the powder is sieved, and powder with a particle size of 15-45μm is selected as the final product. This particle size range is most suitable for plasma spraying; powder that is too small will ablate, and powder that is too large will not melt well.

[0008] Furthermore, the mass ratio of the added Ni, Cr, and Cr2AlC nanoscale solid powders is 64:16:20.

[0009] Furthermore, the auxiliary granulation agent includes a binder and a dispersant, wherein the binder is PVA and the dispersant is PEG.

[0010] Furthermore, the specific proportions of the primary slurry are: solid content 37-42 wt.%, dispersant content 0.5-1 wt.%, and binder content 8-13 wt.%.

[0011] Furthermore, in step S12, the mixing time for wet ball milling is 10-12 hours, and the grinding direction is changed every 20-30 minutes.

[0012] Furthermore, in step S13, the peristaltic pump's peristaltic frequency is set to 8-10 rpm; the inlet temperature of the spray granulator is set to 190-210℃, and the outlet temperature is set to 120-140℃.

[0013] Furthermore, in step S13, the pipeline must be cleaned with deionized water before and after pumping the slurry to prevent blockage.

[0014] Furthermore, the relevant parameters for the spheroidizing process are: voltage 7.7-8.2kV, current 6.8-7.3A, power 52-60kW, and powder feeding rate 28-32g / min.

[0015] On the other hand, the present invention also proposes a metal-ceramic MAX phase composite powder for spraying prepared by the above preparation method.

[0016] The technical solution of this invention has the following beneficial effects: 1. Cr2AlC did not decompose at high temperature. This invention utilizes wet ball milling technology to strictly control the granulation hot air drying temperature and employs inert gas protection during radio frequency plasma spheroidization. This process prevents the decomposition or oxidation of temperature-sensitive Cr2AlC materials throughout the entire process, ensuring their stable existence in subsequent coatings and solving the problem of high-temperature failure of MAX phase powders.

[0017] 2. The powder has good flowability and is uniform and dense. Observation of the powder morphology revealed that the powder has a uniform particle size distribution, high sphericity, and dense structure. Furthermore, XRD test results showed that Cr2AlC was well preserved, meeting the requirements of various thermal spraying technologies.

[0018] 3. Strong process adaptability The composite powder prepared by this invention can be widely used in various thermal spraying technologies such as atmospheric plasma spraying, providing a reliable raw material basis for preparing high-performance MAX phase metal ceramic coatings on the surface of complex parts, broadening the application field of MAX phase materials, and solving the problem that existing MAX phase materials are difficult to use for surface strengthening of complex parts. Attached Figure Description

[0019] Figure 1 The following are morphological diagrams of the raw material powders of the present invention: (a) Ni powder, (b) Cr powder, and (c) Cr2AlC powder. Figure 2 This is a diagram showing the morphology and elemental distribution of the powder obtained by spray granulation according to the present invention; Figure 3 The following images show the surface and cross-sectional morphology of the powder after radio frequency plasma spheroidization according to the present invention: (a) overall powder distribution; (b) magnified view of a typical single powder morphology; (c) powder cross-sectional morphology; and (d) magnified view of a single powder cross-section. Figure 4 The XRD pattern of the powder obtained in this invention; Figure 5 This is a statistical diagram of the particle size distribution of the powder in this invention; Figure 6 The figure shows the test results of the angle of repose of the powder prepared according to the present invention. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0021] This invention proposes a method for preparing metal-ceramic MAX phase composite powder for spraying, the process steps of which are as follows: Weigh out nano-sized raw material powder according to the mass ratio Ni:Cr:Cr2AlC = 1:0.23-0.27:0.30-0.34. Add deionized water to a beaker, then add 1 wt.% of polyethylene glycol (PEG) as a dispersant and 10 wt.% of polyvinyl alcohol (PVA) as a binder, and stir until homogeneous. Then add the above solid powder to make the solid content of the slurry 40 wt.%. Use wet ball milling to thoroughly mix and disperse the slurry for 12 hours, changing the grinding direction every 30 minutes to ensure uniform mixing and prevent powder agglomeration.

[0022] Before pumping the slurry, the pipeline needs to be cleaned with deionized water for 3 minutes. After cleaning, the mixed slurry is pumped into the preheated spray granulator using a peristaltic pump. The peristaltic pump frequency is set to 10 rpm. The inlet temperature of the spray granulator is set to 200 ℃, and the outlet temperature is set to 130 ℃. Stirring is performed simultaneously during pumping (200 rpm) to prevent powder sedimentation. After pumping the slurry, the pipeline is cleaned again with deionized water. The spray granulator performs spray granulation. After granulation, the powder in the powder collection tank is collected and sieved. Primary powder with a particle size greater than 15 μm is sieved using a standard sieve for later use.

[0023] The primary powder obtained by spray granulation requires further debinding and sintering treatment to obtain composite powders with better internal polymerization strength and a smoother surface. The specific steps are as follows: The prepared primary powder is fed into an radio frequency plasma spheroidizer. The parameters for radio frequency plasma spheroidization are: voltage 8kV, current 7A, power 56kW, and powder feed rate 30g / min. To avoid oxidation and decomposition of the MAX phase during spheroidization, argon gas is continuously introduced for protection throughout the process. After spheroidization, powder with a size of 15-45 micrometers (325-800 mesh) is screened as the final product for subsequent spraying.

[0024] Performance test analysis:

[0025] Morphological, elemental, and XRD analyses were performed on the relevant raw materials and the obtained powders. Figure 1 This is a morphology diagram of the raw material powder of the present invention, showing the microscopic morphological characteristics of the basic raw material used in the present invention. The raw material powder has a uniform particle size distribution at the micron and submicron level. Figure 2 The image shows the morphology and elemental distribution of the powder obtained by spray granulation in this invention. The powder exhibits a relatively regular spherical shape, and the elemental distribution reflects the microstructure of the primary powder and the uniform distribution of elements such as Ni, Cr, Al, and C. Figure 3 The images show the surface and cross-sectional morphology of the powder after radio frequency plasma spheroidization. It can be seen that the prepared powder has extremely high sphericity, a smooth surface, and a dense internal structure.

[0026] Figure 4 The XRD pattern of the powder prepared in this invention shows that the Cr2AlC diffraction peak is still obvious in the spheroidized powder, and no obvious decomposition product impurity peaks (such as Al2O3 or Cr2O3 impurity peaks) are seen. Figure 5 The powder particle size distribution statistical diagram of this invention confirms that the powder particle size distribution is uniform, with the particle size distribution concentrated in 20-40μm, meeting the requirement of a normal partial distribution for composite spraying; Figure 6 The image shows the test results of the angle of repose of the powder prepared in this invention. The test result is 35.9°, which proves that it has excellent flowability and fully meets the stringent requirements of thermal spraying process for powder flowability and stability. This powder has been successfully applied to various spraying processes and has obtained a well-bonded and dense composite coating containing MAX phase.

[0027] In summary, this invention combines the advantages of both spray granulation and radio frequency plasma spheroidization. First, basic spherical powder is obtained through spray granulation. Then, the extremely high temperature and rapid cooling rate of radio frequency plasma melt, spheroidize, and densify the powder surface. The resulting powder exhibits extremely high sphericity, a smooth surface, a dense internal structure, and excellent flowability, fully meeting the requirements of thermal spraying processes. Furthermore, this invention achieves uniform low-temperature mixing of raw materials through wet ball milling and strictly controls the hot air drying temperature during granulation. Particularly during the instantaneous high-temperature process of radio frequency plasma spheroidization, the use of inert gas protection successfully prevents the oxidative decomposition of the Cr2AlC MAX phase material, ensuring its stable presence in the final powder and subsequent coatings. (Appendix) Figure 4 The XRD pattern in the sample confirms that the Cr2AlC diffraction peaks in the spheroidized powder are still obvious, and no decomposition product peaks are observed.

[0028] In summary, this invention overcomes the limitations of bulk material forming by designing the material into a powder form suitable for thermal spraying, enabling its deposition on the surface of parts with arbitrarily complex shapes via thermal spraying. Furthermore, it requires only surface modification through spraying, eliminating the need for complete replacement and significantly reducing manufacturing costs. Through optimization of specific spray granulation combined with radio frequency plasma spheroidization processes, a raw material powder highly compatible with the thermal spraying process is obtained, allowing the material to melt, accelerate, and deposit stably and controllably during thermal spraying, forming a high-performance coating.

[0029] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a metal-ceramic MAX phase composite powder for spraying, characterized in that, The process includes the following steps: S1: Spray granulation is used to prepare primary powder, as detailed below: S11: Raw material preparation: Add a certain amount of deionized water to a beaker, then add the auxiliary granulating agent and stir until uniformly dispersed; then add a certain mass ratio of Ni, Cr and Cr2AlC nano-sized solid powders to obtain the initial slurry; S12: Wet ball milling and mixing: The initial slurry is placed in a ball mill jar for thorough ball milling and dispersion mixing to ensure that the powder is fully and evenly dispersed; S13: Spray granulation: The mixed slurry is pumped into a preheated spray granulator using a peristaltic pump for spray granulation. After granulation, the powder in the powder collection tank is collected and sieved to obtain spherical primary powder with a particle size of more than 15μm. S2: Radio frequency plasma spheroidization treatment, as detailed below: S21: Spheroidizing process: The prepared primary powder is fed into an radio frequency plasma spheroidizer for spheroidizing treatment. Argon gas is continuously introduced during the spheroidizing process to avoid high-temperature decomposition of Cr2AlC. S22: Secondary sieving: After spheroidization, the powder is sieved, and powder with a particle size of 15-45μm is selected as the final product.

2. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 1, characterized in that, The mass ratio of the added Ni, Cr and Cr2AlC nanoscale solid powders is 1:(0.23-0.27):(0.30-0.34).

3. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 2, characterized in that, The auxiliary granulation agent includes a binder and a dispersant. The binder is one of PVA, PVP, and PAA; the dispersant is one of PEG, ammonium polycarboxylate, and sodium hexametaphosphate.

4. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 3, characterized in that, The specific proportions of the primary slurry are: solid content 37-42 wt.%, dispersant content 0.5-1 wt.%, and binder content 8-13 wt.

5. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 1, characterized in that, In step S12, the mixing time for wet ball milling is 10-12 hours, and the grinding direction is changed every 20-30 minutes.

6. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 1, characterized in that, In step S13, the peristaltic pump's peristaltic frequency is set to 8-10 rpm; the inlet temperature of the spray granulator is set to 190-210℃, and the outlet temperature is set to 120-140℃.

7. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 6, characterized in that, In step S13, the pipeline must be cleaned with deionized water before and after pumping the slurry to prevent blockage.

8. The metal-ceramic MAX phase composite powder for spraying and its preparation method according to claim 1, characterized in that, The relevant parameters for the spheroidizing process are: voltage 7.7-8.2kV, current 6.8-7.3A, power 52-60kW, and powder feeding rate 28-32g / min.

9. A metal-ceramic MAX phase composite powder for spraying, characterized in that, The powder is prepared by any one of the preparation methods described in claims 1-8, and the powder is in the shape of regular spheres with a particle size distribution of 15-45 μm, and the Cr2AlC phase is intact.

Citation Information

Patent Citations

  • A method for preparing MAX phase ceramic Ti3AlC2 powder by low-temperature sintering using molten salt method

    CN107935596B

  • A method for preparing MAX phase ceramics

    CN110698204B

Cited By

  • A three-dimensional flower-shaped VC x N 1-x / Ti2AlC x N 1-x Construction method of strong microwave absorbing material

    CN122301141A